ANALISIS PENGARUH RASIO LIKUIDITAS, EFISIENSI OPERASI, DAN RASIO SOLVABILITAS TERHADAP KINERJA KEUANGAN PADA PT BANK MAYBANK INDONESIA Tbk PERIODE 2010-2018 - Alma Aprilia; Nina Woelan Soebroto (FInance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2020)
This study aims to analyze the significance of the effect of liquidity ratios, operating efficiency, and solvency ratios both simultaneously and partially on financial performance at PT Bank Maybank Indonesia Tbk. period of 2010-2018. The population in this study is liquidity ratio, operating efficiency, and solvency ratio. The sampling technique using simple random sampling method, obtained samples in this study as many as 3 variables, namely Loan to Deposit Ratio (LDR), Operational Costs compared to Operating Income (BOPO), and Capital Adequacy Ratio (CAR). The data used in this study are secondary data obtained from published quarterly financial reports. The model of analysis used is Multiple Linear Regression, while the data analysis technique uses F Test, Determination Coefficient (Adjusted R²), and t Test. The results of the analysis and discussions show that the variable Loan to Deposit Ratio (LDR), Operational Cost versus Operating Income (BOPO), and Capital Adequacy Ratio (CAR) simultaneously have significant effects on Return On Assets (ROA) at PT Bank Maybank Indonesia Tbk. the period of 2010-2018. Partially, the Loan to Deposit Ratio (LDR) variable has negative and not significant effect on Return On Assets (ROA), while Operational Cost versus Operational Income (BOPO) variables partially have a negative and significant effect on Return On Assets (ROA), as well as variables Capital Adequacy Ratio (CAR) partially has a negative and significant effect on Return On Assets (ROA) at PT Bank Maybank Indonesia Tbk. the period 2010-2018.